Effect of technological factors on freeze-thaw resistance of alkali-activated slag cement concrete in NaCl solution - Krivenko, Pavel; Rudenko, Igor; Konstantynovskyi Oleksandr (AIP Publishing, 2023)
The application of alkali-activated slag cement concrete (hereinafter AASC concrete) is relevant for building constructions which are exploited in aggressive environments with exposed class XF4. It is due to increased freeze-thaw resistance of AASC concrete in water solutions of salts if compared with portland cement concrete. The aim of this work was to investigate the effects of technological factors on porous structure and freeze-thaw resistance of plasticized AASC concrete in NaCl solution. It was shown that increasing of fresh concrete consistency from class S1 up to class S4 due to plasticization by complex admixture “polyorganohydrosiloxane - sodium lignosufonate - polyethylene glycol” as well as application of alkaline component in dry form, in contrast to liquid form, ensures negative changes in porous structure of AASC concrete. These changes cause decreasing of freeze-thaw resistance from mark F500 down to F200. It was revealed that hardening of plasticized AASC concrete under normal conditions (t = 20±2 °С, RH = 95±5%), compared with hardening in water or under steam curing (t = 85±5 °С), ensures more effective porous structure which causes maintained freeze-thaw resistance of F300 in contrast to F200 and F250 agreeable. Effective technological decisions for advanced freeze-thaw resistant of AASC concrete were determined.
Keywords: alcali-activated concrete; porous structure; freeze-thaw resistance; technological factors; agregate state; plasticizer; 666